2012
DOI: 10.3389/fneur.2012.00151
|View full text |Cite
|
Sign up to set email alerts
|

Difficult Diagnoses in Hyperkinetic Disorders – A Focused Review

Abstract: Hyperkinesias are heterogeneous conditions that share the feature of production of involuntary, abnormal, excessive movements. Tremor, dystonia, and chorea are amongst the most common of these phenomena. In this focused review there is a discussion of difficult issues in hyperkinesias. The first one is the differential diagnosis between essential tremor (ET) and Parkinson’s disease (PD). They are readily distinguishable in the majority of patients but in a few subjects ET coexist with parkinsonian features who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Even among experts, two studies addressing inter-observer reliability for diagnosis revealed surprisingly low levels of agreement (Beghi et al 2014; Logroscino et al 2003). One of the main reasons for poor diagnostic recognition is that the dystonias are relatively uncommon, and they are frequently mistaken for more common disorders such as Parkinson’s disease (Cardoso 2012; Jog et al 2011; Lalli and Albanese 2010; Albanese and Lalli 2009; McKeon et al 2008; Schneider et al 2007; Schneider et al 2006) or essential tremor (Fasano et al 2014; Pita Lobo et al 2013; Elble 2013; Cardoso 2012; Schiebler et al 2011; Lalli and Albanese 2010). Children with generalized dystonia are frequently confused with cerebral palsy (Jan 2004; Friedman et al 2012).…”
Section: Can Genetic Testing Improve Dbs Outcomes?mentioning
confidence: 99%
“…Even among experts, two studies addressing inter-observer reliability for diagnosis revealed surprisingly low levels of agreement (Beghi et al 2014; Logroscino et al 2003). One of the main reasons for poor diagnostic recognition is that the dystonias are relatively uncommon, and they are frequently mistaken for more common disorders such as Parkinson’s disease (Cardoso 2012; Jog et al 2011; Lalli and Albanese 2010; Albanese and Lalli 2009; McKeon et al 2008; Schneider et al 2007; Schneider et al 2006) or essential tremor (Fasano et al 2014; Pita Lobo et al 2013; Elble 2013; Cardoso 2012; Schiebler et al 2011; Lalli and Albanese 2010). Children with generalized dystonia are frequently confused with cerebral palsy (Jan 2004; Friedman et al 2012).…”
Section: Can Genetic Testing Improve Dbs Outcomes?mentioning
confidence: 99%
“…Chorea accounts only for about 2% of all NPSLE manifestations, which qualified it as a clinical diagnostic challenge [12]. In practice, the differential diagnosis of chorea is wide and include a long list of hereditary and non-hereditary disorders [13][14][15]. Acquired causes include drugs and toxins, Sydenham chorea, SLE and antiphospholipid (APL) syndrome, chorea gravidarum, stroke and hyperthyroidism [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…12 In practice, the differential diagnosis of chorea is wide and include a long list of hereditary and non-hereditary disorders. [13][14][15] Acquired causes include drugs and toxins, Sydenham chorea, SLE and antiphospholipid (APL) syndrome, chorea gravidarum, stroke and hyperthyroidism. 14,15 In view of the above described wide NPSLE clinical manifestations, pathogenesis is expected to include multiple mechanisms.…”
Section: Discussionmentioning
confidence: 99%